1977
DOI: 10.1136/jnnp.40.1.30
|View full text |Cite
|
Sign up to set email alerts
|

C0-contraction and stretch reflexes in spasticity during treatment with baclofen.

Abstract: SUMMARY Surface electromyograms were recorded from the quadriceps and hamstring muscles of 11 spastic patients during cyclical flexion and extension movements of the knee. A potentiometer strapped to the knee recorded the angle of the joint, the output signal being displayed on an oscilloscope. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 7 publications
(5 reference statements)
0
28
0
2
Order By: Relevance
“…A reduction of background activity unaccompanied by a reduction in the stretch-induced component would be missed by this technique. However, a similar method detected changes in spastic patients after an oral dose of the antispastic drug baclofen (McLellan, 1977 Table 5 Passive stretch responses to sinusoidal displacement in 11 patients: mean±SD. The passive stretch index is the ratio between the amount of EMG generated during passive stretch and the amount generated during passive shortening of the same muscle Despite the acute changes that have been reported to occur in response to short bursts of cerebellar stimulation, no statistically significant changes were seen over the few days of observation (Table 6).…”
Section: Slow Passive Stretch Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction of background activity unaccompanied by a reduction in the stretch-induced component would be missed by this technique. However, a similar method detected changes in spastic patients after an oral dose of the antispastic drug baclofen (McLellan, 1977 Table 5 Passive stretch responses to sinusoidal displacement in 11 patients: mean±SD. The passive stretch index is the ratio between the amount of EMG generated during passive stretch and the amount generated during passive shortening of the same muscle Despite the acute changes that have been reported to occur in response to short bursts of cerebellar stimulation, no statistically significant changes were seen over the few days of observation (Table 6).…”
Section: Slow Passive Stretch Responsesmentioning
confidence: 99%
“…A sine wave target was then set up for the patient, requiring movement through 450 at a frequency of 0.4 Hz. The target appeared on a storage oscilloscope in front of the patient as a stationary display, upon which the signal from the goniometer was superimposed in the manner previously described (McLellan, 1977). After several practice sessions on the first day, the subjects were able to track this target with reasonable accuracy.…”
Section: Quantitative Assessment Of Motor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, considerable training of force production reduces the spasticity, but has little influence on the efficiency of motor commands (Neilson et al 1990). Secondly, there is no conclusive evidence that pharmacological treatment of spasticity improves motor performance (Nathan 1969, McLellan 1977. Finally, the children we tested had spasticity ratings ranging from normal to moderate.…”
Section: Possible Mechanisms Of Impaired Anticipatory Controlmentioning
confidence: 99%
“…Recently, it has been suggested that the major deficit may not be abnormal reflex activity imposing restraints on posture and movement, but that all descending motor commands, including reflex control and muscle contraction signals, are inappropriate. [5][6][7][8][9] In the absence of reflex effects, motor control is thought to be exceedingly poor and not due solely to damage to the descending pyramidal tract. [7][8][9] Evidence supporting the proposition that descending motor commands in cerebral palsy are inappropriate has been based on observing motor control after removal of reflex constraints.…”
mentioning
confidence: 99%